Gender attitudes toward female co-workers at the University of Dhaka, Bangladesh : a case study - Hossain, Dewan Mahboob
This study is an attempt to identify the nature of attitudes towards female co-workers in the workplace. The research looks into specific issues such as financial benefits, recruitment and promotion process, participation in the decision-making process and getting strategic positions where female employees get different treatment compared to male employees in the education sector. In order to fulfil the research objectives, an exploratory study on the faculty members at the University of Dhaka in Bangladesh was conducted. Data were collected through an in-depth interview method which emphasised on a case study technique. The University's faculty members who consisted of ten males and ten females were interviewed. It was found that, in many ways, the gender attitudes and practices that exist in the University of Dhaka reflect the norms and practices of the overall society of Bangladesh. The interviewees commented that the female teachers are more inclined to perform family responsibilities. That is why, in some cases, they lose some financial benefits. As they do not get enough time to socialise with their colleagues, they lag behind in organisational politics and in some cases; they face problems in their recruitment and promotion. In general, Bangladeshi women are introvert and submissive in nature, they do not give their opinions in case of decision-making. They remain more involved in family affairs than their professional affairs. Apparently, they are not eager to hold any strategic position in the University. To these women, family is more vital than work. It was found also that in many cases the job at this University is flexible. As a public university, the University of Dhaka has standardised rules and policies; informally the departments follow many flexible practices. Women on the other hand, take the advantage of this informal flexibility in order to give more time to their families at the expense of their professional work and career.